2016
DOI: 10.3109/13880209.2016.1156708
|View full text |Cite
|
Sign up to set email alerts
|

In vitroimmunomodulatory activity, cytotoxicity and chemistry of some central European polypores

Abstract: Context Some mushrooms of the order Polyporales are known for their immunomodulatory actions. Objective The objective of this study is to evaluate the in vitro phagocytic and cytotoxic effects of extracts from polyporales native to Central Europe. Materials and methods The effects of ethanol extracts from 27 polypore species on opsonized zymosan-induced phagocytosis of isolated human neutrophils were tested by a chemiluminescence method. Colon epithelial cell lines, Caco-2 and HT-29, were used for cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…The mean values of the ratio GAE/extract are expressed as µmol g −1 . In order to compare these values with literature data, [57] Many works report flavonoid concentrations in fungi with a wide range of concentrations. The free flavonoids in ethanol extract of raw Lentinula edodes (Berk.)…”
Section: Hplc Analysis Of the Fungal Extractsmentioning
confidence: 99%
“…The mean values of the ratio GAE/extract are expressed as µmol g −1 . In order to compare these values with literature data, [57] Many works report flavonoid concentrations in fungi with a wide range of concentrations. The free flavonoids in ethanol extract of raw Lentinula edodes (Berk.)…”
Section: Hplc Analysis Of the Fungal Extractsmentioning
confidence: 99%
“…Royoporus badius is a fairly large polypore (up to 15 cm in width) with a dark central or lateral stipe and a slightly hairy base (Glaeser & Smith, 2010), which can be found distributed in (Razaq & Shahzad, 2016). R. badius is also commonly known as the Black-Footed Polypore (Doskocil et al, 2016).…”
Section: The Mushroom Royoporus Badius (Pers) Ab Dementioning
confidence: 99%
“…According to the literature, there have been no known immuno-stimulatory compounds identified from R. badius. Thus far, only two studies have been performed on the ethanol extracts of R. badius, with one exhibiting mild cytotoxic activity against colorectal cancer cell lines (Doskocil et al, 2016), while the other was shown to inhibit the production of proinflammatory cytokines but elicited TH2 response (Koch et al, 2002). Despite…”
Section: Purification Of An Immuno-stimulatory Compound From the Watementioning
confidence: 99%
See 2 more Smart Citations